2019
DOI: 10.1017/trn.2019.4
|View full text |Cite
|
Sign up to set email alerts
|

Southeast Asian Trajectories of Labour Mobility: Precarity, Translocality, and Resilience

Abstract: Within and across Southeast Asian national borders, there has been a growing circulation of labour, capital, people, and goods. Meanwhile, urbanisation, agrarian changes, and liberal economic restructuring have been drawing a large section of the rural population into mobile economies and trade networks. This special issue explores the linkage between mobility and the growing precaritisation of labour resulting from neoliberalised development policies, nationalist citizenship regimes, and discourses, and arbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Global urbanization has absorbed a large number of rural laborers and brings regional prosperity (Davis, 2016;Tappe and Nguyen, 2019). However, global urbanization also causes widespread rural decline, and a large area of rural land has been converted into urban land (Huang et al, 2015;Liu, 2018), the population density of rural areas is generally lower than before (Yang et al, 2016), which has led to an increase in idle rural settlements and a serious shortage of high-quality rural labor resources (Pribadi and Pauleit, 2015;Zhao and Zou, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Global urbanization has absorbed a large number of rural laborers and brings regional prosperity (Davis, 2016;Tappe and Nguyen, 2019). However, global urbanization also causes widespread rural decline, and a large area of rural land has been converted into urban land (Huang et al, 2015;Liu, 2018), the population density of rural areas is generally lower than before (Yang et al, 2016), which has led to an increase in idle rural settlements and a serious shortage of high-quality rural labor resources (Pribadi and Pauleit, 2015;Zhao and Zou, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these transformative processes are not equally experienced as evidenced by the considerable scholarship on precarity and what it means for migrants, those who are the left behind and their villages. Researchers have identified positive migration–development linkages and the increased salience of attachment to place (for those that stay as well as those that must go) that counter‐balance precarity whilst also emphasizing contradictory strains on social and emotional ties caused by chronic absences and rural depopulation (Porst & Sakdapolrak, 2018; Tappe & Nguyen, 2019).…”
Section: Migration and Precarity In Rural Chinamentioning
confidence: 99%
“…The fact that continuous (re)migration is induced by institutional barriers to permanent migration has led some analysts refer to this situation as one of ‘incomplete migration’ (such as Gao et al, 2017) or ‘incomplete proletarianization’ (Chan & Selden, 2014). However, rather than seeing the increasing trend towards translocal householding (Jacka, 2018) as problematic, it may be more useful to ask what the relationship is between translocality and precarity for particular people in particular places (Tappe & Nguyen, 2019; Wilson et al, 2018)? This is salient because, although stretching is a household response to manage poverty and insecurity, straddling the rural and the urban can also prove to be a source of further precarity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Access to mobility is a differentiating factor of migration (Rizvi et al, 2011). In many studies studying resilience in urban cities, transport facilities were found as an influential indicator (Panda & Mishra, 2018; Porst & Sakdapolrak, 2018; Tappe & Nguyen, 2019) while the study on adaptive social protective factors has taken mobilisation, livelihood diversification, risk sharing and informal entrepreneurship as dimensions (Santha et al, 2015). During the development of the theory for resilience, some researchers pointed out that structural adaptation is an important element of protective factors; physical and emotional comfortability and life support facilities such as free hospitals, schools and getting ration cards are some indicators (Michael et al, 2019; Porst & Sakdapolrak, 2018).…”
Section: Review Of Literaturementioning
confidence: 99%